(untitled) (Research, Society and Development, 2024)
The article addresses the impact of affirmative policies on public universities, highlighting how these policies transformed this educational space into a common field. Affirmative policies promoted the inclusion of historically marginalized groups by diversifying both the student composition and the teaching staff. The objective of this article is to analyze how the common potential of the University is realized with the support of public policies for the inclusion and reception of subjects from across society, given that the public university, by adopting these policies, has become a fertile ground to exchange experiences and perspectives, enriching academic debates. To this end, a qualitative methodology of a philosophical-reflexive nature was adopted based on a literature review and documentary analysis. There was a continuous need to face challenges and the need to continue looking for ways to guarantee and maximize the effectiveness of affirmative policies to build more and more truly inclusive and representative universities. The conclusion highlights the public university as a space where diversity is celebrated, challenging prejudices and contributing to the construction of collective knowledge in search of a more fair and egalitarian society.